2020
DOI: 10.1002/lom3.10389
|View full text |Cite
|
Sign up to set email alerts
|

A low‐cost modular control system for multistressor experiments

Abstract: Marine organisms and ecosystems face multiple, temporally variable stressors in a rapidly changing world. Realistic experiments that incorporate these aspects of physiological stress are important for advancing our ability to understand, predict, and manage their ecological impacts. However, the experimental systems needed to conduct such experiments can be costly. Here, we describe a low-cost, modular control system that can be used with seawater sensors and actuators to dynamically manipulate multiple seawat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Pinpoint pH Controller costing $200 [13] . More recently, open-source applications have been published to control aquarium pH, but these devices have invariably been feature-poor, relied on expensive external equipment, or both [14] , [15] , [16] .…”
Section: Hardware In Contextmentioning
confidence: 99%
“…Pinpoint pH Controller costing $200 [13] . More recently, open-source applications have been published to control aquarium pH, but these devices have invariably been feature-poor, relied on expensive external equipment, or both [14] , [15] , [16] .…”
Section: Hardware In Contextmentioning
confidence: 99%
“…The use of Arduino platforms in seawater pH modulation is an important step in advancing this goal [7] , [19] , [20] . Arduino platforms are comprised of programmable physical circuit boards and a companion software—Integrated Development Environment (IDE).…”
Section: Hardware In Contextmentioning
confidence: 99%
“…Together, the Arduino hardware and IDE provide an accessible way for scientists and individuals alike to design and control circuits of varying sizes and complexities. Low et al recently demonstrated this by controlling a complex, robust, and high-performing pH modulation system with an Arduino Uno [19] . While these systems have made important advances in increasing their accessibility, they still carry some of the burdens described above, including relatively high system complexity and the need for custom-made hardware.…”
Section: Hardware In Contextmentioning
confidence: 99%
“…The use of microcontrollers and prototyping tools to undertake laboratory and field monitoring tasks offer a wide range of options to design experimental set-ups. Among other applications micro-controllers allow for automation and handling of data recording, prototyping of mechanical parts and sensors and interfacing with other instruments [14, 15, 5]. Microcontroller prototyping can be use to build systems to execute manual and supervised tasks automatically and/or remotely [16].…”
Section: Introductionmentioning
confidence: 99%